Bonnie Siegler: Designing Her Design Career. - Siegler, Bonnie (linkedin.com, 2016)
In this documentary, learn about Bonnie Siegler—founder of design firms No. 17 and Eight and a Half—as she reflects on her career and what makes a breakout designer successful.